Pendidikan Karakter Berbasis Kecerdasan Ganda Untuk Pembentukan Karakter Anak Dalam Keluarga Di Dasawisma Cempaka I, Sumberawan, Singosari, Malang - Lestari Setyowati; Barotun Mabaroh (Jurnal VOK@SINDO, 2017)
Every kid has differences and uniqueness in terms of the  intelligence. However, not many parents are aware of these. The community counseling about multiple intelligence and its relation toward the character education were conducted in Sumberawan, Toyomarto village, Singosari district, Malang. The purpose of this counseling is to cultivate the parents’ knowledge, especially the mothers,  about multiple intelligence and character education. The subjects were 40 women who joined Dasawisma  meeting. This community service was held on August 2016 to January 2017. The counseling has done in four meetings during pengajian in Dasawisma I Cempaka, Sumberawan. The result of the counseling shows that many women in pengajian Dasawisma I Cempaka were not aware about multiple intelligence and character education. The women started to realize that a kid who has ‘character’ is more valuable than the kid who has only academic  intelligence. They also realized that every kid has their own intelligence that make them unique.